2018
DOI: 10.1016/j.ijheh.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Residential proximity to green spaces and breast cancer risk: The multicase-control study in Spain (MCC-Spain)

Abstract: The association between green spaces and risk of breast cancer is dependent on land-use. The confirmation of these results in other settings and the study of potential mechanisms for the associations observed are needed to advance the understanding on the potential effects of green spaces on health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 35 publications
0
49
2
2
Order By: Relevance
“…Urban green areas help maintain low temperatures in the city during the summer months, improve air quality, and reduce people's stress level (133). An ever-increasing number of studies shown that living in green urban spaces leads to health benefits, including better physical and mental health and a longer life expectancy (134). Studies suggest that the positive influence of nature on health can be observe especially between vulnerable groups such as the elderly, those in rehabilitation for mental disorders, and individuals in crisis rehabilitation (135).…”
Section: Deforestationmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban green areas help maintain low temperatures in the city during the summer months, improve air quality, and reduce people's stress level (133). An ever-increasing number of studies shown that living in green urban spaces leads to health benefits, including better physical and mental health and a longer life expectancy (134). Studies suggest that the positive influence of nature on health can be observe especially between vulnerable groups such as the elderly, those in rehabilitation for mental disorders, and individuals in crisis rehabilitation (135).…”
Section: Deforestationmentioning
confidence: 99%
“…In the older population, contact with parks and green areas has been linked with slower cognitive decline. Moreover, children benefit from living in greener urban areas, such as better spatial working memory, improved attentional control and capacity, and higher academic achievement, particularly in mathematics (136), as well as improved behavior and emotional development, and positive structural changes in the brain (134). Moreover, green areas and parks in childhood have a preventive effect on the risk of developing various mental disorders later in life.…”
Section: Deforestationmentioning
confidence: 99%
“…Physical activity was tested in four studies (14%). Among these four studies, one found a protective effect [46] and three of them reported no association [38], [39], [61]. The other contributing factors identified among all the studies were polycyclic aromatic hydrocarbons (PAHs) (n=4, 14%), mental health (n=2, 7%), reduced anxiety (n=2, 7%), UV radiation (n=2, 7%), pesticides (n=1, 3%) and social engagement (n=1, 3%).…”
Section: • Carcinogenic Riskmentioning
confidence: 98%
“…Two studies reported a protective effect. O'Callaghan-Gordo et al (2018) [39] found direct evidence of a reduced risk of breast cancer for participants who lived with urban green spaces around their residence (300 meters) compared to those who did not. English, Wilson, and Keller-Olaman (2008) [35] interviewed 14 women with breast cancer and identified indirect evidence that natural landscapes including parks can help in the recovery of cancer survivors by inspiring feelings of calmness through a sense of connection with nature.…”
Section: • Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation